2014
DOI: 10.1088/0031-9155/59/20/6141
|View full text |Cite
|
Sign up to set email alerts
|

Towards intra-operative diagnosis of tumours during breast conserving surgery by selective-sampling Raman micro-spectroscopy

Abstract: Breast-conserving surgery (BCS) is increasingly employed for the treatment of early stage breast cancer. One of the key challenges in BCS is to ensure complete removal of the tumour while conserving as much healthy tissue as possible. In this study we have investigated the potential of Raman micro-spectroscopy (RMS) for automated intra-operative evaluation of tumour excision. First, a multivariate classification model based on Raman spectra of normal and malignant breast tissue samples was built and achieved d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 25 publications
2
79
0
1
Order By: Relevance
“…Although fewer Raman measuremens are acquired, which reduces the acquisition time by two orders of magnitude, the spatial resolution of the SSRS images are determined by the first imaging modality. Kong et al showed that it is possible to use integrated confocal auto-fluorescence imaging and Raman spectroscopy for fast detection of tumors in surgical resessions of skin [144] and breast tissue [446]. The auto-fluorescence image provided high resolution, while Raman spectroscopy provided chemical specificity for accuracy diagnosis.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although fewer Raman measuremens are acquired, which reduces the acquisition time by two orders of magnitude, the spatial resolution of the SSRS images are determined by the first imaging modality. Kong et al showed that it is possible to use integrated confocal auto-fluorescence imaging and Raman spectroscopy for fast detection of tumors in surgical resessions of skin [144] and breast tissue [446]. The auto-fluorescence image provided high resolution, while Raman spectroscopy provided chemical specificity for accuracy diagnosis.…”
Section: Applicationsmentioning
confidence: 99%
“…34. Example of selective Raman scanning of (a) skin (scale bar is 0.5 mm) [144] and (b) breast tissue [446] using integrated autofluorescence and Raman microscopy. The series of images for each tissue type includes: auto-fluorescence image(s), segmented image with automated Raman sampling points, Raman diagnosis image(s), and an H&E image.…”
Section: Applicationsmentioning
confidence: 99%
“…[114] Automated segmentation of autofluorescence images was used to select and prioritize sparse sampling points for Raman spectroscopy.T his automated sampling strategy yielded classification models with 100 %s ensitivity and 92 %s pecificity,a nd allowed for objective diagnoses to be made faster than by frozen section histopathology and faster than IR or Raman imaging alone. [115] Raster scanning Raman microspectroscopy of tissue sections is slow with typically 10 000 spectra per mm 2 , which is equivalent to 5hper mm 2 .Selective sampling based on integrated autofluorescence and Raman spectroscopy reduced the number of Raman spectra to 20 spectra per mm 2 ,which is equivalent to an acquisition time of 15 min for an area of 5 5mm 2 . [115] Raster scanning Raman microspectroscopy of tissue sections is slow with typically 10 000 spectra per mm 2 , which is equivalent to 5hper mm 2 .Selective sampling based on integrated autofluorescence and Raman spectroscopy reduced the number of Raman spectra to 20 spectra per mm 2 ,which is equivalent to an acquisition time of 15 min for an area of 5 5mm 2 .…”
Section: Combining Raman Imaging With Other Modalitiesmentioning
confidence: 99%
“…Similarly, the ClearEdge™ system measures tissue-specific electrical properties with promising preliminary data (sensitivity ~85%, specificity ~80%) [25]. Optical spectroscopy techniques such as diffuse reflectance [2628], Raman spectroscopy [29], optical coherence tomography (OCT) [30], spatial frequency domain imaging [31], fluorescence techniques [32] and confocal microscopy [33] all measure tissue response to light at various wavelengths, and whilst preliminary results are promising [34], the diagnostic accuracy of the techniques is inferior to pathological margin assessment and technological developments are required to increase image processing time and improve the ease of use.…”
Section: Introductionmentioning
confidence: 99%